Design of distributed hybrid electric tractor based on axiomatic design and Extenics. (October 2022) - Li, Jinfeng; Wu, Xiuheng; Zhang, Xuemin; Song, Zhenghe; Li, Wenjuan
Abstract: Led by the goals of energy saving and low emissions, tractors need more efficient operations under complex farmland working environments. The powertrain architecture of the tractor has a significant influence on the performance. Therefore, the research on the innovative design of the tractor powertrain architecture can improve the efficiency, energy saving, and environmental protection effects. Based on the creative design method of Axiomatic Design (AD) and Extenics, this paper conducts an innovative design analysis of the powertrain architecture of distributed hybrid electric tractor (DHET). Firstly, AD is used to perform the hierarchical analysis of the tractor powertrain architecture design. Then according to the design content, the design matrix (DM) is established, and the matrix is transformed to extract the 3 × 3 coupling contradiction matrix. Finally, the application of Extenics solves the contradictions in the innovative design of the tractor powertrain architecture. Simulation and prototype experiments have proved that DHET has the advantages of energy saving and emission reduction. This paper analyzes the innovative design of DHET's powertrain architecture, which can provide a theoretical basis and method support for the product's innovative design.